Pemanfaatan Citra Sentinel-1 untuk Deteksi Kerusakan Akibat Gempa Bumi di Kabupaten Cianjur - Firdaus, Arida Vania; Kurniadin, Nia; Itsnani SM, A. Arifin; Arifin, Dawamul (P3KM Politani Samarinda, 2023)
The earthquake in Cianjur Regency, West Java Province, on November 21, 2022 at 13:21:10 Western Indonesia Time. The earthquake's epicenter was at coordinates 6.84° South Latitude and 107.05° East Longitude located about 9.65 km southwest of Cianjur City or 16.8 km northeast of Sukabumi City, with a magnitude of 5.6 at a depth of 10 km. These earthquakes include a shallow crustal tectonic earthquake (shallow crustal earthquake) with a mainshock-aftershock type. Major earthquakes (mainshocks) with a magnitude of 5.6 and aftershocks with a magnitude of 1.2–4.2 and an average depth of about 10 km, of which 5 are felt by the surrounding communities. This study aims to find out the area that suffered damage after the earthquake that occurred in Cianjur Regency, West Java. By using Sentinel-1 satellite image data with ascending and descending orbits in Cianjur Regency, data processing is carried out using ESA SNAP software, then followed by raster to vector, clips of administrative boundaries for Cianjur Regency and making map layouts using ArcGIS software. The results of this study show that 47.10% of the area was affected and suffered severe damage with a total area of 55.73 km2 detected. The total area detected in each district is Agrabinta 0,73 km2; Bojongpicung 0,97 km2; Campaka 1,76 km2; Campakamulya 0,29 km2; Cianjur 0,65 km2; Cibeber 1,42 km2; Cibinong 4,79 km2; Cidaun 2,69 km2; Cijati 0,36 km2; Cikadu 9,47 km2; Cikalong Kulon 1,24 km2; Cilaku 0,60 km2; Cipanas 2,95 km2; Ciranjang 0,18 km2; Cugenang 1,69 km2; Gekbrong 0,90 km2; Haurwangi 0,47 km2; Kadupandak 0,40 km2; Karangtengah 0,65 km2; Leles 1,47 km2; Mande 0,94 km2; Naringgul 10,49 km2; Pacet 1,13 km2; Pagelaran 1,88 km2; Pasirkuda 2,03 km2; Sindangbarang 1,22 km2; Sukaluyu 0,45 km2; Sukanagara 1,10 km2; Sukaresmi 0,81 km2; Takokak 0,57 km2; Tanggeung 0,72 km2; Warung Kondang 0,71 km2. The results of this study were obtained in the form of a post-earthquake damage detection map.